Exploring the Relationship Between Entrepreneurship and Psychological Characteristics, and Corporate Social Responsibility Under Marketization - Shen, Zhengshun; Li, Huaibin; Zhang, Yancai (Frontiers in Psychology, 2021)
The present work aims to explore how and to what extent ventures can bear social responsibilities due to their increasingly important role in social and economic activities. Here, the correlation between entrepreneurship and psychological characteristics of entrepreneurs, and corporate social responsibility is analyzed from the perspective of entrepreneurial entrepreneurs based on marketization theories of enterprise activities. The β value of entrepreneurship in corporate social responsibility is obtained as 0.863 (p<0.001) through a questionnaire survey (QS) and statistical analysis. It indicates that entrepreneurship has a significant positive impact on corporate social responsibility. The regression coefficient of the marketization process is 0.574, and the significance is less than 0.01. The results show that there is a significant positive correlation between the marketization process and corporate social responsibility at the level of 1%. When the marketization process is introduced, entrepreneurship significantly and positively impacts corporate social responsibility (β=0.524, p<0.001), while the marketization process has a great positive impact on corporate social responsibility (β=0.502, p<0.001). However, the coefficient of entrepreneurship and psychological characteristics decreases from 0.863 to 0.524. It reveals that its impact on corporate social responsibility is weakened by the introduction of the marketization intermediary variable, but the overall variation that the model can explain increases to 84.3%. The results show that the marketization process has a significant positive mediating effect on the relationship between entrepreneurship and corporate social responsibility, and entrepreneurship plays a very important role in corporate social responsibility. The content and methods are complete and comprehensive, and the results can provide scientific and effective references for subsequent studies.